THE IMPLICATIONS OF SCHOOL ORGANIZATION AND MANAGEMENT IN PARTICIPATORY MANAGEMENT - Aparecida Gottwitz, Cledir; Loss, Taniele (Revista Gênero e Interdisciplinaridade, 2025)
School management is essential for the organization and functioning of educational institutions, as it influences the quality of learning and the participation of the school community. Participatory management, as an educational administration model, seeks to decentralize decision-making power and encourage shared responsibility among managers, teachers, students, and families. This study aims to describe the implications of school organization and management in participatory management, analyzing how the principal’s decisions regarding resource allocation and the use of school space impact community participation. To achieve this, a bibliographic research was conducted, based on theoretical references discussing school management and the democratization of educational administration. The results indicate that the adoption of participatory practices contributes to decision-making transparency, strengthens the bond between the school and the community, and improves the school environment. However, resistance to participation and the need for managerial training still pose challenges to implementing this model. It is concluded that participatory management is a path to democratic school administration, making it essential to invest in policies that promote this practice.